Integrating Climate Change Adaptation with Local Development: Exploring Institutional Options - Paudel, Naya S; Khatri, Dil B; Ojha, Hemant; Karki, Rahul; Gurung, Niru (Journal of Forest and Livelihood, 2013)
As the effects of climate change become increasingly evident in Nepal, development agencies and policy actors are experimenting with different ways to facilitate climate adaptive development at the local level. This paper analyses the current approaches to local-level adaptation planning and identifies the challenges to and opportunities for integrating climate change adaptation and local development in Nepal. Drawing on field research carried out in two districts of central Terai and two of western hills and supplemented by a review of adaptation plans and national climate change-related policies, this paper demonstrates that the current approach to mainstreaming adaptation in local development is institutionally fragmented and politically naive. There are attempts to involve some community groups, with weak links to local governments, and without enough thinking on how local development vision can be realised in the face of increasing climate risks. We argue that such approach is institutionally misplaced, as there is a tendency to focus certain aspects of adaptation and certain forms of institutions while ignoring others. More importantly, as most efforts are driven by non-state development agencies, there is little political ownership and accountable mechanism to integrate adaptation with local development. It shows that local governments are either ignored or at most marginally involved in the process of local-level adaptation planning. This paper concludes that the current approach—characterized by institutional fragmentation and token involvement of communities and local governments—could paradoxically lead to unaccountable climate governance at the local level. DOI: http://dx.doi.org/10.3126/jfl.v11i1.8606 Journal of Forestry and Livelihood Vol.11(1) 2013 1-13